2020
DOI: 10.20882/adicciones.1431
|View full text |Cite
|
Sign up to set email alerts
|

Apps para dejar de fumar mediante Terapia Cognitivo Conductual. Una revisión sistemática

Abstract: Smoking is a health and economic problem that is difficult to eradicate. Nicotine addicts also often suffer from psychological problems such as depression and anxiety. The recommended treatment according to clinical practice guidelines (CPG) is Cognitive Behavioural therapy (CBT), alone or combined with medication. Currently, health-related apps (m Health) enable wider availability and access to this treatment. The objectives of this study are to carry out a review of the smoking cessation apps that apply CBT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…For example, we found that less than 1 in 5 apps provided evidence-based support for smoking cessation, such as peer support or skill training, including mindfulness and deep breathing, and even fewer provided evidence-based approaches, such as Acceptance and Commitment Therapy or CBT interventions. Similar findings were noted in another recent review, where only 3 apps provided CBT skill training [45].…”
Section: Overviewsupporting
confidence: 87%
“…For example, we found that less than 1 in 5 apps provided evidence-based support for smoking cessation, such as peer support or skill training, including mindfulness and deep breathing, and even fewer provided evidence-based approaches, such as Acceptance and Commitment Therapy or CBT interventions. Similar findings were noted in another recent review, where only 3 apps provided CBT skill training [45].…”
Section: Overviewsupporting
confidence: 87%
“…However, most of the existing mHealth apps on the market were not developed following the recommendations of the USCPG, given that they do not incorporate the brief advice known as the mnemonic rule of the 5 A’s: Ask, Advise, Assess, Assist, and Arrange [ 6 ]. Nor do they include BT [ 18 ] such as CBT [ 19 ], even though scientific evidence indicates that their inclusion improves efficacy rates [ 20 ]. Instead, some apps include acceptance and commitment therapy (ACT) [ 19 ], which is not cited in the CPGs [ 6 , 7 , 21 ].…”
Section: Introductionmentioning
confidence: 99%